Ambition Versus Conscience, Does Corporate Social Responsibility Pay off? The Application of Matching Methods - Shen, Chung-hua - (Journal of business ethics, 2009)
In this article, we examine the effect of corporate social responsibility (CSR) on firms’ financial performance (CSR-effect). Two competing hypotheses, social impact hypothesis and shift of focus hypothesis, are proposed to investigate this issue, where the former suggests that CSR has a positive relation with performance and the latter are opposite. In order to ensure the CSR-effect is not contaminated by other factors or samples are randomly drawn, we employ four matching methods, Nearest, Caliper, Mahala and Mahala Caliper to match the samples of CSR (CSR-firms) and without CSR (NonCSR-firms) with similar characteristics. Although four methods yield slightly different results, firms engaging in CSR activities tend to obtain significantly higher values on pretax income to net sales and profit margin, and adopting CSR at the very least not deteriorate the performance of firms, making our conclusion favors the social impact hypothesis and against shift of focus hypothesis in Taiwan. Thus, ambition and conscience are not conflicting with each other.